Pendampingan Pembelajaran Daerah Terpencil di SD Negeri 1 Tumbang Kuling Kotawaringin Timur Kalimantan Tengah - Akmalia, Hafidha Asni; Indraswati, Dyah; Polonia, Betti Ses Eka (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
School located in a remote areas has a complex educational problems such as limited teachers, inadequate building conditions, difficult road access and even lack of textbooks. This service aims to help SD N 1 Tumbang Kuling Central Borneo in organizing more varied teaching and learning activities using several learning methods. The Community Service Team introduced guessing method, team games tournament, and singing to students to motivate them in learning despite their limitations. The students can follow the given learning process well and feel happy to be able to learn through the existing methods. This kind of service activity can be an inspiration for the community to assist the government in overcoming the problem of education disparities in schools in a remote areas.